2021
DOI: 10.1038/s41598-021-82674-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with failure of total ankle arthroplasty: a nationwide cohort study

Abstract: We conducted a nationwide population-based cohort study to identify the risk factors associated with failure of total ankle arthroplasty (TAA). We included 2,914 subjects who underwent primary TAA between January 1, 2010, and December 31, 2016, utilizing the database of the Korean National Health Insurance Service. Failure of TAA was defined as revision TAA or arthrodesis procedures. An increased risk of TAA failure was observed in the < 65 age group versus the ≥ 75 age group [adjusted hazard ratios (aHR) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Our results are consistent with previous studies, which have shown that body weight has a negative prognostic role in total ankle arthroplasty. 3,5,29,35,40,53,62,64…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with previous studies, which have shown that body weight has a negative prognostic role in total ankle arthroplasty. 3,5,29,35,40,53,62,64…”
Section: Discussionmentioning
confidence: 99%
“…The details of the selection process are presented in Figure 1. As a result, 9 studies with a total of 10 388 patients were eligible for inclusion in the quantitative analysis [6][7][8]15,16,26,53,62,64 and 28 in the narrative synthesis. [1][2][3][4][5][9][10][11]13,14,[17][18][19]23,25,29,[34][35][36]40,44,47,48,50,51,56,59,65…”
Section: Search and Selectionmentioning
confidence: 99%
“…A correlation between increased BMI and perioperative outcomes has been reported, particularly surgical site infections and renal and respiratory complications, in patients undergoing total knee arthroplasty [ 11 ]. The risk of total ankle arthroplasty failure has increased in patients with obese [ 12 ]. Midgley et al highlighted in a literature review that this growing cohort of struggling patients is currently supported by existing care frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between increased BMI and perioperative outcomes has been reported, particularly surgical site infections and renal and respiratory complications, in patients undergoing total knee arthroplasty [9]. The risk of total ankle arthroplasty failure has increased in patients with severe obesity having a BMI ≥ 30 kg/m 2 [10]. Midgley et al highlighted in a literature review that this growing cohort of struggling patients is currently supported by existing care frameworks.…”
Section: Introductionmentioning
confidence: 99%